Performance of the BD CTQx and GCQx Amplified Assays on the BD Viper LT Compared With the BD Viper XTR System. Issue 9 (September 2015) - Van Der Pol, Barbara; Hook, Edward W.; Williams, James A.; Smith, Bonnie; Taylor, Stephanie N.
<x xml:space="preserve">Abstract</x> Abstract We evaluated the BD Viper LT System for detection of Chlamydia trachomatis and Neisseria gonorrhoeae using samples collected from symptomatic patients that included urine, vaginal swabs, and cervical samples in liquid-based cytology media. Results were compared with those obtained using the BD Viper XTR platform. The positive and negative percent agreements for all sample types were at least 95.8% and at least 96.4% for chlamydia and gonorrhea and at least 95.0% when both organisms were present, respectively. This medium throughput system performs well compared with a high-throughput platform and may offer smaller health care facilities the opportunity to test for these infections locally.